COMPATIBILITY LEVEL OF SEVEN INDONESIAN LOCAL JATROPHA (Jatropha curcas Linn.) CROSSING ACCESSION - Maftuchah, Maftuchah; Zainudin, Agus; Heliyanto, Bambang; Sudarmo, Hadi (Journal of Agroecology, 2015)
Jatropha curcas Linn., is one of the oil plant producers, which can be processed to be the substitute fuel for diesel. The purpose of this research is to gain information of accession crosses compatibility level from different selected Jatropha. The study was conducted using seven accessions of Indonesia Jatropha planting material, which has a high productivity expectations, the HS-49, SP-16, SP-38, SP-8, SM-33, SP-34, and SM-35. The seven accessions were selected mass. Jatropha accessions used as an elder in the course of this research came from Gardens Jatropha Plant Germplasm Collection located in Asembagus–Situbondo. The crossings between seven accessions are not entirely successfully producing fruit and seeds. The crossing between SP-38 X HS-49 produced the highest number of fruits and seeds and followed by the crossing between SM-35 X HS-49. Of all the 42 crossing combinations, there are 14 crossing combinations that do not produce fruit and seeds at all.